The 1999 Catholic directory of the Philippines containing status of the Catholic Church in the Philippines as of January 1, 1999. (Catholic Bishops' Conference of the Philippines and Claretian Publications, 1999)
A directory for the Catholic Church in the Philippines. It provides a hierarch of the Catholic Church and lists the Catholic institutions by territory and association. It also has indices to parishes and names.